2019
DOI: 10.1002/chem.201902549
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 1,4‐Thiazepane‐Based Curcuminoids with Promising Anticancer Activity

Abstract: Curcumin, the main component of turmeric (Curcuma longa) is known to display an interesting bioactivity profile, including pronounced anticancer properties. However, its low bioavailability, metabolic instability and nonspecific activity are concerns that have to be addressed before curcuminoids can be considered for therapeutic applications. Within that framework, intensive research has been carried out in the last decades to develop new curcumin derivatives, generally centered on standard modifications of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 62 publications
0
19
0
1
Order By: Relevance
“…The fluorinated curcuminoids were synthesized to evaluate their inhibitory activities against HepG2 and compare with the activities of 1,3-diketone curcumin analogues. The presence of fluorine atom(s) in aromatic rings displayed close (7,9) or lower (8, 10) inhibitory activities respecting to compounds (1)(2)(3). As mentioned, the para-substituted À OH group is responsible for generating phenoxyl radical which is the crucial species for apoptosis.…”
Section: In Vitro Cytotoxicity Against Hepg2mentioning
confidence: 91%
See 3 more Smart Citations
“…The fluorinated curcuminoids were synthesized to evaluate their inhibitory activities against HepG2 and compare with the activities of 1,3-diketone curcumin analogues. The presence of fluorine atom(s) in aromatic rings displayed close (7,9) or lower (8, 10) inhibitory activities respecting to compounds (1)(2)(3). As mentioned, the para-substituted À OH group is responsible for generating phenoxyl radical which is the crucial species for apoptosis.…”
Section: In Vitro Cytotoxicity Against Hepg2mentioning
confidence: 91%
“…Therefore, the lower activities of fluorinated curcuminoids could be observed. Note that compounds (7,9) bearing fluoro groups at meta-positions in aromatic rings remain cytotoxicity, suggesting the effect of fluoro meta-substitution on their inhibitory activities.…”
Section: In Vitro Cytotoxicity Against Hepg2mentioning
confidence: 99%
See 2 more Smart Citations
“…Curcumin (1), a constituent of turmeric powder derived from the rhizome of C. longa, is an attractive compound with broad-spectrum capacities including anti-oxidant 5 , anti-inflammatory 6 , and antitumour 7 activities. In particular, many studies reported that curcumin exhibited anti-cancer activity in a wide range of human cancers [8][9][10][11][12][13][14][15] . In addition, curcumin is pharmacologically safe as large quantities of curcumin, up to 10 g per day, can be consumed without inflicting toxicity 16 .…”
Section: Introductionmentioning
confidence: 99%